Implikasi Perubahan Peraturan Usia Menikah Pada Pengajuan Dispensasi Nikah - Hanifah, Umi; Chusna, Ufiq Ashfiyatul (Komparatif: Jurnal Perbandingan Hukum dan Pemikiran Islam, 2023)
Marriage law in Indonesia in regulating the minimum age limit for marriage previously adhered to Law Number 1 of 1974, then changes occurred in article 7 which equates the minimum age limit for marriage for men and women, namely 19 years. Meanwhile, the Compilation of Islamic Law (KHI) as a guideline for determining the laws of Muslim communities, in article 15 states that the age limit follows Article 7 of the 1974 Marriage Law, so by changing the reference article, the minimum restriction by KHI also changes. Even though there are additional special conditions stipulated in the new article, in general, the ratification of Law No. 16 of 2019 has not had much impact on public awareness about the importance of not getting married at an early age, this can be seen from the number of marriage dispensation applications. So that it has the potential for someone to carry out a marriage under the hand.